1983
DOI: 10.1002/cber.19831160443
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 2]‐Cycloaddition von Iminoboran und Iminophosphan

Abstract: [2 + 21-Cycloaddition Products from lminoborane and IminophosphaneThe iminoborane Bu -B = N-tBu (la) and the iminophosphanes R2N -P = N -R' (2a, b) undergo a cyclisation to the corresponding 1,3,2,4-diazaphosphaboretidines (3a, b). Wie anhand zweier Diazadiboretidine vom Typ 4 mittels Rontgenstrukturanalyse nachgewiesen wurde, liegt bei dieser Verbindungsklasse wohl im allgemeinen ein planarer Vierring mit koplanaren Nachbaratomen vor. Auch die NPNP-Vierring-Verbindung 5a ist planar gebaut, die beiden Nachbara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Compounds 2a − e and 3a − e are the first examples and four-membered rings where both boron and nitrogen are tetracoordinated. However, related cycloadducts with tricoordinate boron and nitrogen have been obtained with aminoiminophosphines and iminoboranes …”
Section: Discussionmentioning
confidence: 99%
“…Compounds 2a − e and 3a − e are the first examples and four-membered rings where both boron and nitrogen are tetracoordinated. However, related cycloadducts with tricoordinate boron and nitrogen have been obtained with aminoiminophosphines and iminoboranes …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Indeed, while CBD is extremely reactive,i ts BN analogue,1 ,3,2,4-diazadiboretidine (DADBT,F igure 1b)i sachemically stable and isolable species when sterically bulky groups are attached to the boron and nitrogen atoms for kinetic protection. [22][23][24][25][26][27][28] Quantum chemical calculations have suggested that the parent DADBT (B 2 N 2 H 4 )i nt he S 0 state has an onaromatic or weakly Hückel antiaromatic character depending on slight structural differences. [29] Form ore detail, DADBT in the S 0 state with a( quasi-)planar rhombic structure is ac losed-shell species,i nw hich the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are localized on the nitrogen and boron atoms,r espectively (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…For structurally related compounds, this was rationalized by the close proximity of the CH 3 -groups to the lone pair of electrons on the adjacent P atom. 20 Due to the same reason, two relatively large 4 J (PH) coupling constants (3.4 and 3.7 Hz) were observed for the isomer of 9 in which the SiCl 3 -group points towards the face of the four-membered ring (9′). 19 The chlorosubstituted Si atom in 9 appears as doublet resonance in the typical range in the 29 Si NMR spectrum (δ(Si) = −27.3 ppm) 21 It is assumed, that 7 is obtained from 9 via an intermediate of type 10 which forms upon rotation 22 of the P-N bond involving the SiCl 3 -substituted N atom and inversion 23 of one of the P centers in 9 (Scheme 2).…”
Section: Resultsmentioning
confidence: 91%